ANALISIS KINERJA MANDOR DALAM MENERAPKAN MANAJEMEN KUALITAS PADA PROYEK PEMBANGUNAN NUSA DUA GOLF RESORT KAWASAN BTDC - NUSA DUA, BALI - Sukaratha, Gde; Yansen, I Wayan; Astawa Diputra, I Gde (Jurnal Ilmiah Teknik Sipil, 2012)
Physical development of a hotel will try to present the best quality to its consumer. So that every hotel operator will release of hotel quality standard to manage. This standard become reference and go into effect in the entire world where that hotel network reside in, including development of Nusa Dua Golf Resort to be managed by Novotel group - Accor. In order to get standard quality, a “mock up” building was built, before the hotel development to be continued. Long design process have been undertaken by designer consulting to put “quality” as a major construction process. Later in the construction execution the contractor is expected to follow the quality standard set up by consultant. The contractor will be supervised by Construction Management Consultant and Quantity Surveyor Consultant This research will study about quality process ability of foreman representing contractor. Project Quality Management which consist of Quality Planning, Quality Control and Quality Assurance were used in course of evaluation. The primary research data were collecting using questionnaire instrument and observation. Data colected were evaluated by descriptive analysis, for descriptions about the level ability of foreman. This study revealed that the relationship between foreman ability and education, experience, motivation and dicipline in applying quality management in this construction project were extremelly low and were not significant. Therefore, quality management trainning to foreman is recommended.
Keywords: foreman performance, quality